Data for: Probing the Influence of Water on Silica Surface Modification during Amine Grafting for Enhancing CO2 Adsorption - Ogunedo, Briggs; Rees, Gregory; Nabavi, Ali (Cranfield University, 2026)
Amine-grafted adsorbents have long been considered a promising option for carbon capture, though there remains considerable scope to improve their adsorption performance, as well as their hydrothermal and hydrochemical properties. This study investigated the influence of water addition on silica surface modification during amine grafting with (3-aminopropyl)triethoxysilane (APTES) on silica supports. 29Si cross polarisation magic angle spinning (CPMAS) nuclear magnetic resonance (NMR) spectroscopy was employed to investigate the widely held belief that the presence of water during grafting increases the surface silanol content of silica-based sorbents. Conversely, the Brunauer–Emmett–Teller (BET) and NMR results indicated that water enhances APTES diffusion and facilitates the hydrolysis of ethoxy groups, thereby accelerating the condensation reaction with surface silanol groups and enabling a more complete reaction with the silica surface. Additionally, the reduction in Q4 sites, which represent fully condensed silica atoms, further supports this mechanism, as water-mediated hydrolysis produces reactive silanol groups for bonding with silica atoms within the silica bulk. These finding explained the phenomena previously observed in wet grafted synthesis, which led to improved sorption kinetics, enhanced thermal stability, better regenerability, interaction strength, enhanced CO₂ adsorption and selectivity.
This study aims to investigate how the addition of water during grafting affects the surface chemistry of the support material. Accordingly, it examined how potential changes in surface chemistry influence adsorption kinetics, stability, interaction strength, and adsorbent selectivity during multicomponent adsorption.
Keywords: Amine grafting; Wet grafting; Silanol density; Siloxane bridge; CO2 capture; Adsorption; Net-zero